Analisis Pengembangan Usaha Kecil, Dan Menengah Pada Kesejahteraan Masyarakat Kampung Bordir Kecamatan Beji (Ditinjau Dari Maqashid Syariah) - Widya Setiyawati; Renny Oktafia (Jurnal Ilmiah Ekonomi Islam, 2021)
Kampung Embroidery, Beji Subdistrict, Pasuruan Regency is one of the districts of East Java that thinks about the welfare of the community through creative efforts and Pasuruan is also known to be many creative women who are active in earning a living. In a situation of limited job opportunities, it turns out that in the area of ​​Embroidery Village, there are many Home Industry border craftsmen.. MSMEs have an important role in the economy and business development in Indonesia. This research method uses descriptive qualitative research methods and interactive data analysis. The results show that through economic growth a country is able to change its economic conditions for the better in accordance with maqashid sharia and can improve the welfare of the community.